(untitled) (Journal of Organizational Psychology, 2020)
We know little about how and when social capital is shared from individuals to their teams and how this sharing might facilitate team innovative performance. This paper offers three important contributions. First, I argue that individuals’ willingness to share their external ties with their teammates is not automatic. Secondly, I propose that individuals with greater levels of team-related relational and cognitive social capital, tertius iungens orientation, and team member interdependence are more likely to share their ties with their team. Finally, I examine the interactive role of external and internal team ties in promoting team innovative performance.